Protein quality, nutrition and health - Calvez, Juliane; Azzout-Marniche, Dalila; Tomé, Daniel (Frontiers in Nutrition, 2024)
Dietary proteins are energy macronutrients providing nitrogen, amino acids (AA), and energy. AAs are the main nitrogen-containing compounds in the body and are the precursors for the synthesis of body proteins and of several other AA-derived molecules. Among the 20 AAs included in protein sequence, 9 are classified as "nutritionally essential" or "indispensable" AA (IAA) because they cannot be synthesized in the body and must be provided by the diet. IAAs are limiting components for protein synthesis. An adequate intake of protein is required to support growth, maintenance, body functions, health and survival. Official definition of protein requirement is based on nitrogen balance. Protein quality is related to the capacity of protein to provide an adequate quantity of nitrogen and of each of the 9 IAAs for the different physiological situations in humans. Protein source is considered high quality for humans when the protein is readily digested, simultaneously providing an adequate quantity of nitrogen and of each of the 9 IAAs to maintain an adequate metabolic AA pool. The most accurate assessment of protein quality of foods for humans is through metabolic studies that measure nitrogen balance. The protein quality score is the ratio of the content of each IAA in the food and in a reference profile. This score corresponds to the calculated composition of a protein which, when meeting protein requirements, simultaneously meets the requirements of each of the 9 IAAs. AA scores as predictors of protein quality must be adjusted for protein and AA availability.